2014
DOI: 10.1111/joor.12142
|View full text |Cite
|
Sign up to set email alerts
|

A double‐blind randomised clinical trial of two techniques for gingival displacement

Abstract: Knowledge about security and the potential damage originated by the gingival displacement techniques has not been described through randomised clinical studies. This crossover, double-blind, randomised clinical trial evaluated clinical and immunological factors related to conventional and cordless gingival displacement (GD) techniques, and patients' perceptions in 12 subjects with the employment of 2 GD techniques: conventional (gingival cord + 25% AlCl3 astringent gel) and cordless (15% AlCl3 astringent-based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 17 publications
0
21
1
1
Order By: Relevance
“…In three articles, cord techniques were less efficient in controlling bleeding and to lesser extent, when nonimpregnated cords were used. On the other hand, Sarmento et al reported no difference in hemostasis control between cord and cordless gingival retraction techniques, possibly due to the synergistic use of a hemostatic agent (Viscostat; Ultradent).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In three articles, cord techniques were less efficient in controlling bleeding and to lesser extent, when nonimpregnated cords were used. On the other hand, Sarmento et al reported no difference in hemostasis control between cord and cordless gingival retraction techniques, possibly due to the synergistic use of a hemostatic agent (Viscostat; Ultradent).…”
Section: Resultsmentioning
confidence: 99%
“…Four studies commented on the influence of cords or paste on gingival/periodontal health. Three studies reported greater traumatic injury when cords were packed in the sulcus, resulting in an increased tendency for gingival recession, although Sarmento et al failed to identify any significant difference between both techniques.…”
Section: Resultsmentioning
confidence: 99%
“…The results exhibited no statistically significant difference in the gingival recession, PI, BOP, and AL from the baseline to 12 months of Merocel placement. A double‐blind randomized clinical trial of two techniques was undertaken by Sarmento et al . Cord with astringent and Expasyl paste were incorporated, and neither of the two techniques resulted in any significant change in the periodontal indices.…”
Section: Resultsmentioning
confidence: 99%
“…Gingival retraction methods can cause an inflammatory response mainly due to mechanical trauma or the chemical agents present in the astringents . According to Feng et al, the gingival retraction can result in increased levels of pro‐inflammatory cytokines, which can cause gingival recession.…”
Section: Aimsmentioning
confidence: 99%
“…Furthermore, this was recently confirmed in a double‐blind randomized clinical trial in which gingival cord with 25% aluminium chloride astringent gel and a 15% aluminium chloride astringent‐based paste cordless displacement material were compared. Neither technique resulted in worse periodontal indices at 10 days after retraction; however, lower post‐treatment levels of inflammatory cytokines were present after the use of the paste cordless displacement material compared with the cord . Further research in this area is needed.…”
Section: Optimizing Esthetic Outcomesmentioning
confidence: 99%